Cervical Intraepithelial Lesions: A Systematic Review - Villanueva-Sosa, Adán Joél (Revista Arbitrada Interdisciplinaria de Ciencias de la Salud. Salud y Vida, 2026)
Cervical cancer remains a major cause of morbidity and mortality among women worldwide, particularly in low- and middle-income countries. This study aimed to systematically synthesise published evidence on the reported prevalence ranges of cervical cytological abnormalities—atypical. A systematic literature review was conducted in accordance with PRISMA guidelines. Higher proportions of abnormal cytology were consistently reported in resource-constrained settings with limited organised screening programmes. Strengthening organised screening programmes, improving cytotechnologist training, and enhancing follow-up systems are essential to reduce variability and disease burden. Limitations include heterogeneity in study designs and reporting standards, as well as exclusion of non-accessible publications.